Development of an Indirect ELISA to Distinguish between Porcine Sapelovirus-Infected and -Vaccinated Animals Using the Viral Nonstructural Protein 3AB - Zuchang Zhong; Benqiang Li; Jie Tao; Jinghua Cheng; Ying Shi; Pan Tang; Jiajie Jiao; Huili Liu (Current Issues in Molecular Biology)
Porcine sapelovirus (PSV) is a new pathogen that negatively impacts the pig industry in China. Affected pigs experience severe diarrhea and even death. Vaccination is used to control disease outbreaks, and sensitive diagnostic methods that can distinguish infected animals from vaccinated animals (DIVA) are essential for monitoring the effectiveness of disease control programs. Tests based on the detection of the nonstructural protein (NSP) 3AB are reliable indicators of viral replication in infected and vaccinated animals. In this study, the recombinant PSV 3AB protein was expressed by a prokaryotic expression system, and an indirect ELISA method was established. Serum samples from healthy animals, immunized animals, and infected animals were evaluated. The ELISA method identified 3AB with high sensitivity (99.78%) and specificity (100.0%), and no cross-reaction was observed with serum antibodies against porcine reproductive and respiratory syndrome virus (PRRSV), infection with classical swine fever virus (CSFV), pseudorabies virus (PRV), bovine viral diarrhea virus (BVDV), porcine epidemic diarrhea virus (PEDV), or foot-and-mouth disease virus (FMDV). The ELISA method described here can effectively distinguish infected and vaccinated animals and is an important inexpensive tool for monitoring serum and controlling PSV.